2016
DOI: 10.1002/cam4.798
|View full text |Cite
|
Sign up to set email alerts
|

Antitumor activity of combined endostatin and thymidine kinase gene therapy in C6 glioma models

Abstract: The combination of Endostatin (ES) and Herpes Simplex Virus thymidine kinase (HSV‐TK) gene therapy is known to have antitumor activity in bladder cancer. The potential effect of ES and TK therapy in glioma has not yet been investigated. In this study, pTK‐internal ribosome entry site (IRES), pIRES‐ES, and pTK‐IRES‐ES plasmids were constructed; pIRES empty vector served as the negative control. The recombinant constructs were transfected into human umbilical vein endothelial cells (HUVECs) ECV304 and C6 rat gli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 29 publications
1
5
0
Order By: Relevance
“…We confirmed the versatility of our sp-RRV-mediated double suicide gene transfer system by investigating the preclinical antitumor efficacy and bystander effects of the combined vectors, spRRVe-sEF1α- TK and sRRVgp-sEF1α- CD , in seven patient-derived GSCs, each of which possessed unique properties (e.g., growth rates and genomic profiles). Our method synergistically halted cell division and induced cancer cell death, anti-angiogenesis, and TAM depletion in orthotopic patient-derived glioblastoma xenografts, which were consistent with the previously reported antitumor activities of the TK/GCV and CD/5-FC systems [8,9,14,23,38,48]. Similarly, recent studies have demonstrated that the fusion of TK and CD with GCV and 5-FC synergistically improves therapeutic efficacy via the enhancement of cytotoxicity and bystander effects [30,34,49].…”
Section: Discussionsupporting
confidence: 89%
“…We confirmed the versatility of our sp-RRV-mediated double suicide gene transfer system by investigating the preclinical antitumor efficacy and bystander effects of the combined vectors, spRRVe-sEF1α- TK and sRRVgp-sEF1α- CD , in seven patient-derived GSCs, each of which possessed unique properties (e.g., growth rates and genomic profiles). Our method synergistically halted cell division and induced cancer cell death, anti-angiogenesis, and TAM depletion in orthotopic patient-derived glioblastoma xenografts, which were consistent with the previously reported antitumor activities of the TK/GCV and CD/5-FC systems [8,9,14,23,38,48]. Similarly, recent studies have demonstrated that the fusion of TK and CD with GCV and 5-FC synergistically improves therapeutic efficacy via the enhancement of cytotoxicity and bystander effects [30,34,49].…”
Section: Discussionsupporting
confidence: 89%
“…The fragment also inhibits FGF-2 and VEGF-induced EC proliferation and migration [86,87]. Relying on its anti-angiogenic properties, endostatin displays potent anti-tumoral effects [88,89,90,91]. Remarkably, the treatment with the recombinant fragment induces vessel normalization and, as a consequence an improved chemotherapy efficacy [92].…”
Section: Collagens: a Major Source Of Anti-angiogenic Fragmentsmentioning
confidence: 99%
“…For example, herpes simplex virus‐1 thymidine kinase (HSV‐TK) is the most comprehensively studied suicide gene therapy against malignant glioma . HSV‐TK catalyses the phosphorylation of nucleoside analog ganciclovir (GCV), converting it into a toxic metabolite which inhibits DNA replication and cell proliferation, thus inducing cell apoptosis . The developing therapy regimen requires supporting diagnostic methods that can efficiently evaluate early treatment responses.…”
Section: Introductionmentioning
confidence: 99%